Diastereoselective Construction of Densely Functionalized 1‐Halocyclopentenes Using an Alkynyl Halo‐Prins/Halo‐Nazarov Cyclization Strategy. Issue 47 (24th October 2017) - Alachouzos, Georgios; Frontier, Alison J.
Abstract: A diastereoselective two‐step strategy for the synthesis of densely functionalized 1‐halocyclopentenes with several chiral centers has been developed. In the first step, a multicomponent alkynyl halo‐Prins reaction joins an enyne, a carbonyl derivative, and either a chloride, bromide, or iodide to produce a cyclic ether intermediate. In the subsequent step, the intermediate is ionized to generate a halopentadienyl cation, which undergoes an interrupted halo‐Nazarov cyclization. The products contain three new contiguous stereogenic centers, generated with a high level of stereocontrol, as well as a vinyl halide allowing for additional functionalization. The strategy creates two new carbon–carbon bonds, one carbon–halide bond, and one carbon–oxygen bond. Abstract : A two‐step strategy has been developed for the synthesis of densely functionalized 1‐halocyclopentenes with a high level of stereocontrol. First, a multicomponent alkynyl halo‐Prins reaction joins an enyne, a carbonyl derivative, and either chloride, bromide, or iodide to produce a cyclic ether intermediate. Then, the intermediate is ionized to generate a halopentadienyl cation, which undergoes an interrupted halo‐Nazarov cyclization.